2009
DOI: 10.1007/s00404-009-1187-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically assisted myomectomy versus abdominal myomectomy in short-term outcomes: a prospective study

Abstract: In selected group of patients, LAM as minimally invasive approach is an attractive alternative to conventional laparotomic myomectomy, offering significant advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 27 publications
0
62
2
Order By: Relevance
“…A prospective study has shown this approach to have perioperative advantages over traditional laparotomy. 58 …”
Section: Surgical Technique For Laparoscopic Myomectomymentioning
confidence: 97%
“…A prospective study has shown this approach to have perioperative advantages over traditional laparotomy. 58 …”
Section: Surgical Technique For Laparoscopic Myomectomymentioning
confidence: 97%
“…Moreover, it is undoubtedly that some surgical times of the laparoscopic approach may make it easier to perform abdominal surgical interventions otherwise more complex and invasive [16].…”
Section: Discussionmentioning
confidence: 99%
“…Traversing the endometrial lining during myomectomy is thought to increase the risk of uterine rupture during pregnancy or delivery [21,22]. In adult women with amenable uterine leiomyomata (eg, isolated tumors with partial involvement of the myometrium), myomectomy can be performed laparoscopically with or without robotic assistance [23,24]. However, given the extent of this patient's uterine leiomyoma, which based on preoperative imaging appeared to consume the entire width of the myometrium, laparoscopic or robotic myomectomy was not considered a surgical option.…”
Section: Discussionmentioning
confidence: 99%